ISLAMIC WORLDVIEW DAN LAHIRNYA TRADISI ILMIAH DI INSTITUSI PENDIDIKAN ISLAM - Sarjuni Sarjuni (TA'DIBUNA: Jurnal Pendidikan Agama Islam, 2019)
This article seeks to describe that Islam is not just a religion that pays attention to issues of credo and ritual, but it is also a worldview that brings a change for Muslims. As an Islamic way of life, it has an integrated view of physical and non-physical realities. The verses of the Koran are seminal concepts that project an Islamic view of the universe and life which are referred to as Islamic natural views. It has a different view from the views of other religions and civilizations. Conceptually, Islam as a worldview is closely related to all human activities as social, intellectual, and religious beings. As a system of belief, thought, and values, it has the power to change the conditions of civilization. So that in history, its presence has been able to generate scientific traditions through the earliest educational institutions known as Madrasas as-Suffah. From this Madrasa ash-Suffah, ashab ash-suffah (scientific community) developed, This scientific community is needed for the emergence of scientific traditions. The existence of this scientific tradition which later generates to major scholars in the fields of Kalam Science, Tafsir, Hadith, Fiqh, Sufism, etc., which in subsequent developments were able to give birth to polymath Muslim scientists, namely scientists who have expertise in various fields of science at once.Keywords: Islamic Worldview, Scientific Traditions, Science